Sequential DBD plasma-assisted tandem tri-electrodes Fenton process for enhanced antibiotics treatment and denitrification - Kien Tiek Wong; So Yeon Yoon; Seok Byum Jang; Nurhaslina Abd Rahman; Choe Earn Choong; Young June Hong; NAH, IN WOOK; Yeomin Yoon; Eun Ha Choi; Min Jang (Elsevier BV, 2024)
Ozone generated by dielectric barrier discharge (DBD) plasma has the potential for water treatment; however, its limitations, including water solubility, performance in complex matrices, and resistance to some pollutants. This study explored a sequential DBD plasma assisted by a tandem tri-electrode Fenton (S-PEF) process, using a three-stage treatment approach for degrading antibiotics (sulfamethoxazole, SMX; amoxicillin, AMX; and norfloxacin, NOF) in continuous flow mode for 220-bed volumes. Initially, antibiotics such as SMX and AMX underwent degradation in DBD plasma gas, which housed the mixing chamber. The more resilient NOF was removed by hydroxyl radicals (radical dotOH) in the following anodic chamber of the tandem trielectrodes by Fenton assisted oxidation. The continuous cyclic redox regeneration of Fe in tandem trielectrodes prevents secondary Fe sludge pollution. Finally, NO3-N and NO2-N were denitrified into N2 with 95 % selectivity in a cathodic chamber using copper oxide nanowires. This sequential treatment is crucial to mitigating the competitive effects of CO32？ and humic acid in wastewater since O3 is less susceptible to them compared to radical dotOH. The S-PEF completely degraded all antibiotics regardless of water temperature (10 and 25 °C) compared to sole plasma treatment. Finally, toxicity assessments using an ecological structure？activity relationship (ECOSAR) and E. coli disinfection assays showed a significant reduction in toxicity. This study highlights the promising potential of the S-PEF as an advanced technology for wastewater treatment.